Enhanced ions and electrons transmission enables high-performance KxMnO@C cathode for hybrid supercapacitors. Issue 12 (15th June 2022) - Chen, Lina; Zheng, Xiaowen; Hao, Chongyang; Sun, Qidi; Si, Pengchao; Ci, Lijie; Wei, Jun
Abstract: Manganese oxides have been regarded as one of the most promising electrode materials for energy storage systems. Especially, they can be used as battery-type electrodes in hybrid supercapacitors to achieve high energy density and power density at the same time. In such an application, the redox reaction on the battery-type electrodes needs to speed up to match the fast charging-discharging process of the counter capacitive electrodes. Herein, we intercalated K + ions into MnO2 to enlarge the interlayer space as channels for ion diffusion, and coated the particles with carbon layer to achieve fast charging/discharging ability. The obtained Kx MnO@C particles delivered a high specific capacitance of 1039 F g −1 in 5 M LiTFSI aqueous electrolyte. Coupled with activated carbon anode, the hybrid supercapacitor showed outstanding energy and power density.